The Principal's Business In Improving the Quality of Islamic Education (Case Study at SDIT AZ Jambi City) - Ariza Arsul; Anne Johanna; Huang Congzhao (P3M IAI Nusantara Batang Hari, 2021)
Efforts of Principals in Improving the Quality of Islamic Education at SDIT AZ Jambi. The background of this study is that Islamic educational institutions, especially schools, still experience obstacles in improving the quality of education. This can be seen from various aspects ranging from curriculum objectives, educational personnel, learning methodologies, infrastructure facilities, and evaluation, as a whole still contains problems that until now have not been completely solved. Therefore, in improving the quality of Islamic education in schools, strong leadership from the principal is needed. The purpose of this study is to evaluate: 1) the efforts of principals in improving teacher professionalism, 2) the efforts of principals in improving the quality of educational infrastructure, 3) the efforts of principals in improving the quality of learning processes, and 4) the efforts of principals in improving student achievement at SDIT AZ Jambi. This research uses descriptive- qualitative methods and approaches by using three research instruments, namely interviews, observations, and documentation studies. The results show that: 1) SDIT AZ Jambi has experienced a good improvement in quality. Under the leadership of a reliable principal, SDIT AZ Jambi can now become one of the Islamic educational institutions that are at the forefront and able to produce high -performing outputs. 2) The efforts of principals in improving the quality of education, namely: a) improving the professionalism of teachers by creating rules for teachers, placing teachers according to their abilities, giving trust and motivation, conducting coaching. b) improve the quality of infrastructure facilities through the improvement of infrastructure facilities, cooperate with other institutions/agencies in the procurement of infrastructure facilities. c) improve the quality of the learning process by developing an Islamic educational model, improving learning methods, managing the quality of the curriculum. d) improve student achievement by holding consolidation activities, additional lessons, cooperation with learning guidance institutions, guiding teachers to create effective learning, creating a disciplined school culture, providing various extracurriculars, sending students in various competitions.